52.0k views
0 votes
Anyone know how to do BOTH of these? Thanks!

Anyone know how to do BOTH of these? Thanks!-example-1
User Rtpg
by
5.6k points

2 Answers

2 votes
The answer to the top one is 243.
User Alyson
by
5.0k points
2 votes

Question 1:

We have to simplify the expression
((3^(3) * 3^(4))^(2))/(3^(3) * 9^(3))

=
((3^(3))^(2) * (3^(4))^(2))/(3^(3) * (3^(2))^(3))

(Using the law of exponent,
(a^(m))^(n)=a^(m * n))

=
(3^(6) * 3^(8))/(3^(3) * 3^(6))

Cancelling
3^(6) from the numerator and denominator.

=
(3^(8))/(3^(3))

(Using the law of exponent,
(a^(m))/(a^(n))=a^(m-n))

=
3^(8-3)

=
3^(5)

= 243

Question 2:

The average mass of an adult human = 65 kg

The average mass of an ant =
4 * 10^(-6) kg (Since the unit of average mass of ant is not mentioned, i have assumed it as kg)

Let the number of ants be 'n'.

According to the question,

Average mass of adult human = n
* Average mass of ant


65 kg = 4 * 10^(-6) kg * n


n=(65)/(4 * 10^(-6))


n=16.25 * 10^(6)


n=1625 * 10^(4)

So,
1625 * 10^(4) ants are needed to equal the mass of one average human.

User Michalbrz
by
6.1k points